A Droop Based Control Strategy for Bidirectional Power Regulation in Hybrid Acmc Microgrids - Rojas-Lobos, F; Espina-Gonzalez, E; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2021)
Hybrid Alternating Current (AC) and Direct Current (DC) microgrids have been in the spotlight in the last years because they allow connection of AC and DC resources and reduces multiple power conversion in single AC or DC microgrids. The AC and DC stages are connected through interlinking converters, which manage the power transference among both sub-microgrids using droop control strategies for each single AC or DC microgrid. This paper proposes a threestage droop control strategy to regulate the power inside the sub-microgrids at the same time that bidirectional AC-DC power transference is enabled. Simulation results obtained with a hybrid microgrid model composed of five generation units are presented to validate the effectiveness of this proposal.. © 2021 IEEE.